Applied control theory for embedded systems - Wescott, Tim (Newnes, 2006)
Many embedded engineers and programmers who need to implement basic process or motion control as part of a product design do not have formal training or experience in control system theory. Although some projects require advanced and very sophisticated control systems expertise, the majority of embedded control problems can be solved without resorting to heavy math and complicated control theory. However, existing texts on the subject are highly mathematical and theoretical and do not offer practical examples for embedded designers. This book is different;it presents mathematical background with sufficient rigor for an engineering text, but it concentrates on providing practical application examples that can be used to design working systems, without needing to fully understand the math and high-level theory operating behind the scenes. The author, an engineer with many years of experience in the application of control system theory to embedded designs, offers a concise presentation of the basics of control theory as it pertains to an embedded environment. * Practical, down-to-earth guide teaches engineers to apply practical control theorems without needing to employ rigorous math * Covers the latest concepts in control systems with embedded digital controllers * The accompanying CD-ROM contains source code and real-world application examples to help users create fully working systems.
Keywords: Embedded computer systems -- Design and construction.; Digital control systems -- Design and construction.; elektronické knihy; electronic books